How does growth mindset affect mental health of high school students during the COVID-19 epidemic? The role of grit and coping strategies - Zhang, Libin; Qi, Huan; Wang, Chenxu; Wang, Tian; Zhang, Yunyun (Frontiers in Psychiatry, 2022)
Background: Teenagers’ mental health is affected by the COVID-19 epidemic resulting from the social isolation and lockdown. The implicit theory of thoughts-emotion-behavior states that individuals with a growth mindset believe that thoughts, emotions, and behaviors can be enhanced through effort, and are conducive to developing quality of grit and positive coping strategies. The aim of this study was to explore the role of grit and coping strategies in the impact mechanism of the growth mindset on teenagers’ mental health during the COVID-19 epidemic period. Methods: 1564 participants (Mage = 17.02, 760 boys, 804 girls) from three high schools in China completed questionnaire survey, including Self-report Questionnaire, Growth Mindset Scale, The Short Grit Scale, and Ways of Coping Questionnaire to evaluate mental health, growth mindset, grit, and positive coping strategies respectively. Results：The results showed that the indirect effect of growth mindset on mental health through grit is not significant, the indirect effect of growth mindset on mental health through coping strategies is significant. The chain mediating effect of growth mindset on mental health through grit and coping strategies is significant, which indicate grit and coping strategies play chain mediating roles between growth mindset and teenagers’ mental health. Conclusions: Teenagers with a growth mindset focused on improving their ability to cope with setbacks during the COVID-19 pandemic, and adjust themselves by adopting more positive and flexible coping strategies to maintain mental health.